Les compétences transversales d’un point de vue ergologique - Louis Durrive (Recherches en Éducation)
How must we consider generic competencies in training, and especially in vocational training? To answer this important question in our view, one must take into account the subjectivity - and therefore the activity - of the person developing his (or her) skills: how does he (or she) commits to his (or her) own action in order to carry it out? Various competency-based approaches have disregarded this subjective dimension of action, or on the contrary they have substantified it as something existing apart from actions - in other words: as something one could call for artificially in some predefined actions. In this paper we contend that, to legitimately speak of generic competencies ‎in the area of vocational training, it is necessary to refer them each time to various specific concrete actions they are engaged into.